PENERAPAN MODEL BIMBINGAN KELOMPOK DENGAN TEKNIK PEER GROUP DALAM MENINGKATKAN PERILAKU DISIPLIN MEROKOK - Arief Rachman (JIV-Jurnal Ilmiah Visi, 2015)
This research aims at discovering empirical description of the implementation of group counselling with peer group technique in improving the smoking behavior of female juveniles in Panti Sosial Bina Remaja (PSBR) Bambu Apus, Jakarta Timur. The research conducted as from September through December 2012 was a simple experiment with one group pretest-post test design. The research subjects are seven juveniles supervised by PSBR Bambu Apus, Batch 72. The result of the group counselling was achieved by pre-test and post-test showing the improvement of 19.52 or 33.23 %. The research concluded the implementation of group counselling with peer group technique proves the improvement of smoking behavior of juveniles in PSBR Bambu Apus, Jakarta.